(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Studies have shown that ABO blood groups and demographic traits influence susceptibility to type 1 diabetes mellitus (T1DM) and can be used in combination with insulin therapy to reduce the disease’s burden. However, geographical variations exist in the influence of demographic traits and ABO blood groups on susceptibility to diseases and thus require establishing it in every locality. This study determined the influence of demographic traits and ABO blood groups on the prevalence of T1DM in Lagos, Nigeria. A structured checklist was used to collect data from the health records of non-obese 150 type 1 diabetic patients at Ayobo Primary Health Center, Lagos. The results revealed that males, with 88 participants (52.7%), constituted the majority, while females had 62 (41.3%). The age group 40 years and older had the highest proportion of participants with 37 (24.7%), followed by 31-40 years with 32 (21.30%), 21-30 years with 30 (20%), 11-20 years with 27 (18%), and 1-10 years with 24 (16%). Christianity had the highest with 74 participants (49.3%), followed by Islam with 71 participants (47.3%), and traditional religion with 5 participants (3.3%). Eight (5.3%) of the participants were primary school graduates; 34 (22.7%) were secondary school graduates; and 108 (72%) were tertiary school graduates. The Yoruba ethnic group, with 77 participants (51.3%), was the most prevalent, followed by Igbo with 50 (33.3%), and Hausa with 3 (2.0%). ABO blood group A and B (positive and negative) individuals were the most diabetic and expressed the most severe cases, while group O positive and AB negative individuals were the least diabetic. T1DM prevention should be a priority for blood group A and B residents.